THE AFFIXATON OF INDONESIAN-ENGLISH MIXED COMPLEX WORDS FOUND IN TWITTER SELECTED TWEETS - Fauziah, Rizqi (2014)
This research paper entitled The Affixation of Indonesian-English Mixed Complex Words in Twitter Selected Tweetsaims to reveal the process of affixation especially in prefixation in which prefixes are attached to Indonesian-English mixed complex words shaped by English base. In particular, this study attempts to investigate the grammatical meanings and the morphophonemic rules that have occurred in the complex words shaped by English Base found in Twitter. The study employs a qualitative-quantitaive method to describe and interpret the data. In this study, the data were the selected tweets which are purposively chosen in order to answer the research questions. The theories of Ramlan (2009) and Kridalaksana (2009) are applied as the basis of identifying the kinds of prefixes, the grammatical meanings and the morphophonemic rules that have occurred in the Indonesian-English mixed complex words found in Twitter. The findings reveal that there are two kinds of prefixes found in the study, namely prefix-non-simulfix (51.28%) andprefix-simulfix (48.72%). The most frequent prefix-non-simulfix is prefix {di-} (57.50%) while the most frequent prefix-simulfix is prefix {nge-}(57.9%). In relation to its meaning, each prefix that is attached to English base has various meanings which depend on its context. Prefix-non-simulfix has 9 meanings such as action/to do base,passive base, undeliberate action of base, most of base, able to do something related to the base, has been done something related to the base, having base, in a condition of baseand as base. Meanwhile, prefix-simulfixhas 6 grammatical meanings such as action/to do base, feeling like base, has the characteristic, go to/aim, becoming base, and making of base. Moreover, both prefixes also undergo the alteration if they are attached to a particular initial base. For instance, prefix-non-simulfixmeN- undergoes the alteration into [mən-], [məɲə-], and [mə-] if it meets particular initial phonemes. Meanwhile, prefix-simulfix N- nasalizes into[ɲə-], [ɲ-], [ň-] and [n-] in particular environments. Based on the findings, it can be seen that the users of Twitter tend to mix Bahasa Indonesia with other languages especially in English.They create new colloquial Indonesian and its rules. It shows that the effects of social media have seriously wrecked Bahasa Indonesia by ruining the rules of how to use Bahasa Indonesia properly. Penelitian ini membahas studi afiksasi pada kata komplex yang terdiri awalan Bahasa Indonesia dan dasar Bahasa Inggris. Penelitian ini menginvestigasi makna secara gramatikal dan kaidah morfofonemik prefiks pada pada kata kompleks campuran Bahasa Indonesia dan Bahsa Inggris di media sosial Twitter. Penelitian ini menggunakan metode deskriptif kualitatif untuk mendeskripsikan dan menginterpretasi data. Dari data yang ditemukan, ada dua jenis prefiks yang ditambahkan sebelum dasar Bahasa Inggris yaitu prefiks yang tidak bersimulfiks (51.28%) dan prefiks yang bersimulfix (48.72%). Data yang ditemukan menunjukan bahwa setiap imbuhan memiliki beberapa makna gramatikal tergantung pada konteks dan jenis dasarnya. Selain itu, data menunjukan bahwa prefiks yang tidak bersimulfiks dan prefiks yang bersimulfiks mengalami proses morfofonemik karena mengalami perubahan pada prefiks atau pada dasar. Sebagai contoh, prefiks {meN-} akan berubah menjadi [mən-], [məngə-], dan [mə-] apabila bertemu dengan dasar dengan awalan fonem tertentu. Sedangkan awalan yang bersimulfiks N- berubah menjadi [ɲə-], [ɲ-], [ň-] dan [n-] apabila menemui fonem dasar awal tertentu. Temuan menunjukan bahwa para pengguna Twitter menciptakan bahasa gaul dan aturannya. Hal itu memperlihatkan bahwa dampak dari penggunaan media social telah merusak Bahasa Indonesia dengan merusak aturan bagaimana menggunakan Bahasa Indonesia yang baik dan benar.